Peningkatan Hasil Belajar Penyelesaian Soal Cerita KPK dan FPB dengan Model Polya di Kelas V SDN 01 Pandam Basasak, Kapau - Azlina, Nur; Ahmad, Syafri (Universitas Negeri Padang, 2016)
This study aims to describe the improvement in learning outcomes of problem solving for students on mathematics with the Polya model). This type of research is Classroom Action Research (CAR) using a qualitative and quantitative approach. The subjects of this study were teacher and fifth grade students. The research was carried out in two cycles. Research procedures include, planning, implementation, observation, and reflection. Research results from cycle I to cycle II. (a) The average learning planning value of Cycle I 74.95% increased to 96.4% in cycle II. (b) the average value of the implementation, the activity of the teacher in the first cycle, which is 72.5% has increased in Cycle II to 92.5%. In the activities of Cycle I students with an average of 73.75% increased in Cycle II to 90%. (c) The results of improving student learning in problem solving in Cycle I with an average value of 72.96 increased in cycle II to 84.61 Thus the Polya model can improve the results of problem solving skills in mathematics learning in Class V SDN 01 Pandam Basasak Kapau.